Systemic immune activation in hereditary cancer predisposition syndromes: a cross-sectional study - István Kelemen; Klaudia Horti-Oravecz; Anikó Bozsik; Tímea Pócza; János Papp; István Likó; Patrícia Neuperger; Fanni Balogh; Ágnes Kemény; Petra Nagy; Viktória Vereczki; Szonja Polett Pósa; et al. (BMC Medicine, 2026)
Abstract Background Immune surveillance mechanisms contribute to the elimination of precancerous lesions in hereditary cancer predisposition syndromes (HCPSs). Methods By combining single-cell transcriptomics, multiparametric mass cytometry and cytokine profiling of the systemic immune environment in 391 individuals among whom 227 are living with HCPSs we investigated phenotypic alterations in cancer-free individuals with HCPS. Results A decrease in peripheral B cell abundance and their more differentiated phenotype have been confirmed both in breast cancer patients with germline pathogenic variants in BRCA1 (gpath( BRCA1 )) and in patients living with Lynch syndrome (LS). Pre-cancer women with gpath( BRCA1 ) exhibited an activated phenotype of multiple immune cell lineages, similar to those with manifest disease. In LS, B cell phenotypes exhibited the largest changes in response to cancer eradication, while increased peripheral IL-6 levels was detected even in presymptomatic individuals with LS. Conclusions HCPS-specific differences in the phenotype of the systemic immune system might be leveraged in future risk-reducing strategies.